Intra-Day Arbitrage Opportunities in Foreign Exchange and Eurocurrency Markets. - Chang, Rosita P; Rhee, S Ghon (Journal of Finance, 1992)
The authors have two primary objectives in this study. First, they examine the frequency of attaining simultaneous equilibrium on spot and forward foreign exchange markets and on domestic and foreign securities markets. Second, they measure the profitability of covered interest arbitrage and one-way arbitrage. The authors' empirical analysis has been conducted using real-time quotations. The empirical results indicate that the markets are efficient in the sense that profit opportunities from traditional covered interest arbitrage are rarely available and the frequency of attaining simultaneous market equilibrium is surprisingly low, thus opening the door for one-way arbitrage.